Point Prevalence Study of Use and Consumption of Antibiotics by using Anatomical and Therapeutic Chemical Classification and Defined Daily Dose Methodology in Tertiary Care Hospital - Kumar, Amit; Krishna, VN Vamsi; Sindusha, P; Susritha, M (Indian Journal of Pharmacy Practice)
Objectives: The aim of this study is to identify the use and consumption of antibiotics in tertiary care hospital by using Anatomical and therapeutic chemical classification and Defined daily dose index. Material and Methods: A point prevalence study was conducted at tertiary care hospital. A total of 640 patients were included in this study and taken from different medical departments. Patient’s demographic and biological data was collected from the medical records. Antibacterial drugs were classified according to ATC/ DDD index and antibiotic consumption was measured by DDD/ 100 Patient days. Results: The mean age of 640 patients was 44 (sd 13.53). About 78% of the antibiotics are prescribed from the NLEM (2018-2019). The consumption of antibiotics is higher in departments like surgery (92.18%), Orthopaedics (87.5%) and General medicine (81.25%) followed by Gynaecology (78.13%) and Pulmonology (50.2%). The DDD/ 100 Patient days in Gynaecology were 19.4, in Pulmonology unit 45.2, in surgical unit 24.82, in General medicine unit 33.6 and in Orthopaedics 30.23. Discussion: In our study the rate of utilisation of antibiotics was found to be 78%. Broad spectrum antibiotics like cephalosporin’s and aminoglycosides are prescribed frequently in the hospital which leads to increase in the microbial resistance. The DDD of ceftriaxone (1250) and cefixime (400) is higher when compared to aminoglycosides i.e. amikacin (700). Conclusion: The DDD of cephalosporins is higher when compared to other antibiotics. Inappropriate use of antibiotics leads to increase in the microbial resistance. Prescribers are forced to use broad spectrum antibiotics when other antibiotic therapy options are not available.
Keywords: DDD/100 Patient days; ATC classification; NLEM; Antibacterial drugs; Medical units and microbial resistance.